DETERMINATION OF IRRIGATION PROCEDURES IN GROWING CORN (SILAGE) WITH WASTEWATER (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
2 years of scientific-practical research work was carried out in the development of the irrigation regime (norm) of the corn (silage) crop of Bukhara city wastewater, and the results were highlighted. If the soil moisture before irrigation is 70-70% relative to the marginal field moisture capacity, seasonal irrigation in meadow-alluvial soils is 2723 m3/ha in the first year, the number of irrigations is 4 times, and in the second year, the seasonal irrigation norm is 4044 m3/ha, the number of irrigations is 5 times. soil moisture before irrigation was 70-80% relative to the marginal field moisture capacity. In the first stagnant year, the seasonal irrigation norm was 2814 m3/ha, the number of irrigations was 5 times, in the second year, the seasonal irrigation norm was 4071 m3/ha, the number of irrigations was 6 times.